Nutritive value of by-product from dates for use in animal feed - Gasmi-Boubaker A.; Ben Ismail H.; Boubaker B.; Zine Elabidine E. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
In date packing and processing operations a number of by-products become available, therefore they should be used to improve the economics of the operation as a whole and to decrease disposal problems and costs. The main byproducts of date industry are cull dates and date pits from packing operations, and pits and press cakes from date processing. This study aims to evaluate the chemical composition and in vitro dry matter (DM) digestibility of pits, cull date and infested date for incorporation in animal feed and to evaluate the effect of tannins on in vitro fermentation through the use of tannin biding polyethylene glycol (PEG). The statistical results revealed a highly significant difference between by-products. Pits presented relatively high content of crude fiber (37.72% DM), crude protein (8.87% DM), and fat (6.29% DM) but low in vitro DM digestibility (22.78%). However cull date and infested dates had a high digestibility (87-89%). They were relatively high in carbohydrates but poor in crude protein (4.48-4.73% DM) and fat (0.42-0.45% DM). Because of their high carbohydrate content and relatively low fiber, cull and infested dates have a high energy value, as high as that of barley grain.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)